THE ROLE OF GAMES IN TEACHING ENGLISH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the importance of teaching English and the role of games in teaching young learners. It discusses the problems of teaching English to young learners in educational organizations. Some different kinds of qualitative research methods; group games, physical games, scavenger hunt games, activities like “Simon says” were conducted in this study. Multi-method triangulation is used throughout in this study. It was determined from the data that games should be employed in second language learning classrooms in terms of providing an atmosphere for EFL learners in which there are fun, motivation and high learning performance.